Exploring feminist egalitarian discourse and sex work for the social work curriculum: A critical pedagogy - Flynn, Susan; Sweeney, Leigh-Ann (My University, 2026)
This article presents theoretical exposition of feminist egalitarian discourse for social work education by drawing on the research findings of 15 sex workers in the Republic of Ireland. The study claims that feminist social work is not considered mainstream across social work programmes despite social work’s commitment to human rights and social justice. The paper presents the complexities of feminist standpoint when discussing sex work in Ireland in its current binary context of the neo-abolitionist perspective. We argue for a revised critical feminist egalitarian pedagogical approach to the social work curriculum. We apply a feminist standpoint epistemology and an interpretivist/feminist qualitative framework to examine (1) feminist social work (2) feminist theory and sex work (3) and feminist egalitarian discourse for social work education. The positionality of feminist egalitarian discourse within the social work curriculum has capacity to improve social work`s commitment to social justice.
PUBLISHED
DOI: https://doi.org/10.1332/20498608Y2024D000000045
Keywords: social work education, feminist discourse, sex work, social justice; Inclusive Society; Sexuality and sexual health; Education; Gender; Social exclusion